Development and Implementation of the Technical Accident Prevention Subsystem for the Smart Home System - Teslyuk, Vasyl; Beregovskyi, Vasyl; Denysyuk, Pavlo; Teslyuk, Taras; Lozynskyi, Andrii (International journal of intelligent systems and applications, 2018)
The structure of the technical accident prevention subsystem for the smart home system has been developed in the article. The subsystem model based on Petri network, model based on neural network and physical model using the Arduino microcontroller have been realized in the development process. The subsystem research results with the use of the developed models, soft- and hardware tools are also presented.